2021
DOI: 10.3390/geriatrics6030078
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Discharge in Geriatric Long Staying Inpatient and Emergency Department Admissions: A Descriptive Study

Abstract: Background: This study describes long length of stay during emergency department (ED) visits and hospital admissions, barriers to discharge, and discharge solutions for geriatric patients. Methods: We conducted a retrospective medical record review of a random sample of 150 ED patients and 150 inpatients with long length of stay (LOS) encounters. Cohorts were characterized by demographics, social determinants of health (e.g., health insurance, housing), medical comorbidities at admission, discharge care coordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…ED boarding was also found to be directly related to increases in 10‐ and 30‐day mortality rates 2 . Furthermore, studies have shown that ED patients who experience long lengths of stay (LLOS) are more likely to belong to the oldest age bracket of 85–95 years old, reflecting a population likely to live in a skilled nursing facility (SNF) or assisted living facility (ALF) 4 …”
Section: Introductionmentioning
confidence: 99%
“…ED boarding was also found to be directly related to increases in 10‐ and 30‐day mortality rates 2 . Furthermore, studies have shown that ED patients who experience long lengths of stay (LLOS) are more likely to belong to the oldest age bracket of 85–95 years old, reflecting a population likely to live in a skilled nursing facility (SNF) or assisted living facility (ALF) 4 …”
Section: Introductionmentioning
confidence: 99%